PENENTUAN JENIS VEGETASI LOKAL UNTUK PERLINDUNGAN TEBING SUNGAI SIAK DENGAN DESAIN EKO - ENGINEERING TANPA TURAP - Sittadewi, Euthalia Hanggari (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Eco Ã¢â‚¬â€œ engineering without civilÃ¢â‚¬â„¢s construction design for the Siak riversideÃ¢â‚¬â„¢s protection canÃ‚Â be applied at the part of river has riversideÃ¢â‚¬â„¢s weak damaged. The riversideÃ¢â‚¬â„¢s protectionÃ‚Â system with eco Ã¢â‚¬â€œ engineering without civilÃ¢â‚¬â„¢s construction as the effort to make strongerÃ‚Â the riverside with vegetation components. The used of local vegetation is the best choiceÃ‚Â for eco Ã¢â‚¬â€œ engineering system. The identification of vegetation on the Siak riverÃ¢â‚¬â„¢s corridor asÃ‚Â long as desa Merempan Hilir to choose the plants to make the eco Ã¢â‚¬â€œ engineering withoutcivil constructionÃ¢â‚¬â„¢s design has been done. Some kind of plants have been choosen i.e :rumput teki (Cyperus rotundus), rumput kumpai (Hymenachne acutigluma) rumput akarÃ‚Â wangi (Vetiveria zizanioides), karangkunan (Ipomea carnea), bambu kuning (BambusaÃ‚Â vulgaris), pandan (Pandanus, sp), bintaro (Cerbera manghas), rengas (Gluta renghas),kempas (Koompassia malaccensis), jawi Ã¢â‚¬â€œ jawi (Ficus, sp) and meranti (Shorea, sp).Key words : desain eko Ã¢â‚¬â€œ engineering tanpa turap, perlindungan tebing, tanaman lokal